Pollen biology and metaxenic studies on early maturing grape (Vitis vinifera) genotypes - DHAKAD, ASHOK; PATEL, V B; SINGH, S K; VERMA, M K; MISHRA, GYAN P; MHETRE, V B; KUMAR, CHAVLESH; SINGH, RAKESH; RAJKUMAR, S; GAIKWAD, KISHOR (The Indian Journal of Agricultural Sciences, 2024)
The present experiment was conducted during 2020–21 and 2021–22 at ICAR-Indian Agricultural Research Institute, New Delhi to study the impact of open-, self-, and cross-pollination on metaxenic traits (berries) and the incidence of cleistogamy in grapes (Vitis vinifera L.). Seven different cross-combinations were used on the grape variety Pusa Navrang, which were planted at 3 m × 3 m spacing and trained on the Y-trellis training system. The experiment was laid out in a randomized block design (RBD) with four replications. The incidence of cleistogamy, berry set, retention percentage, and the metaxenia effect of pollen grains in different grapevine varieties, namely, Pusa Navrang (PN), Black Muscat (BM), Pusa Swarnika (PS), Beauty Seedless (BS), Perlette (PER), Male Hybrid (MH), were studied. Also, pollen quantity and viability were determined for the different grapevine varieties under study. Depending on the genotypes and whether the fruit set is obtained inside the covered flowers, cleistogamy was confirmed. A significantly higher berry set (40–85%) and retention (32–77%) were recorded in open- and self-pollinated flowers. The total number of pollens/anther in six grape genotypes ranged from 7916.62–23832.02, whereas the maximum active pollen rates were noted in the Male Hybrid (70.01%) and Black Muscat (66.80%). The pollens from the Beauty Seedless genotype exhibited significant enhancement of metaxenic traits such as berry set, retention, and size in Pusa Navrang. Therefore, utilizing Beauty Seedless as a pollen parent in grape breeding programmes holds promise for enhancing berry set and overall berry quality, thus enhancing the hybridization efficiency.